(untitled) (Hematology Meeting Reports, 2009)
Autoimmune diseases (AD) have a higher prevalence in women, particularly during their childbearing age. A growing interest is being paid to the possible consequences of maternal disease and associated treatment on the fetus and newborn infant. If maternal disease is characterized by the presence of IgG isotype autoantibodies, these can cross the placenta with possible antibody-mediated damage to the fetus. In addition, immunosuppressive and other drugs administered to the mothers during pregnancy might affect the fetal and neonatal immune system development. Finally, mothers disease and/or treatment could be related to neuropsychological alteration reported in some of their children.